Enhancing Students Writing Performance Through POW+TREE Strategy - Reski Pilu; Opik Dwi Indah; Suhardi Suhardi (Jurnal Studi Guru dan Pembelajaran, 2018)
This research aims to find out whether or not the use of POW+TREE technique is enhance the students’ writing argumentative paragraphs. This research apply pre-experimental research. The population of this research is the sixth semesters of English Education Study Program of Universitas Cokroaminoto Palopo in academic year 2016/2017. There are 6 classes in the sixth semester of Universitas Cokroaminoto Palopo and the researcher use simple random sampling to take the sample and the total sample is 20 students. Based on the data that shows as the pretest mean score is 35,90 and the mean score of posttest is 58.50. So the result of this research shows that the used of POW+TREE technique in teaching writing argumentative paragraph is able to enhance the students’ ability in writing argumentative paragraphs.